QUALIDADE PÓS-COLHEITA E ALTERAÇÕES BIOQUIMICAS DE DUAS CULTIVARES DE BATATA SUBMETIDAS A ESTRESSE TÉRMICO - SUCHORONCZEK, ADRIANO (2016)
High temperatures during the transport process can be subject potato tubers to thermal stress, that can affect tuber quality and shelf-life. Our aim was to evaluate the effects of simulated heat stress on decay of potato tubers through post-harvest physicochemical characteristics and activity of SOD (Superoxide dismutase), CAT (Catalase) and POX (Peroxidase). We evaluate two cultivars, Ágata, used for in natura consumption and Atlantic, intended for industrial processing. The treatments consisted of four temperatures (20, 30, 40 and 50 °C) with four exposure times at each temperature (0, 3, 6 and 12 hours) and the design was completely randomized. Evaluations were initiated 48 hours (2 days) after application of treatments. At intervals of 7 days (2, 9, 16, 23, 30 and 37 days), we evaluated the weight loss of the tubers, decay tuber firmness, soluble solids, dry matter content, pH and titratable acidity. At two, nine, and 37 days after application of treatments were conducted evaluations of SOD, CAT and POX. It was no effect to grow for all sources of variation and only was no effect of treatments for the dry and CAT matter. Cultivar Atlantic showed higher sensitivity to heat stress with greater loss of fresh weight and higher percentage of tubers degradation. With increasing temperature and exposure time were observed reduction in firmness, increase in soluble solids and titratable acidity values, reducing the pH and increasing decay of tubers and the weight loss.